Illicit Penile Augmentation: A Short Review in a Single Institution - Hamzan, Muhammad Izzuddin; Jeffrey, Mohamad Jeremi; Halim, Ahmad Sukari (Ukrainian Journal of Nephrology and Dialysis, 2020)
Illicit penile augmentation is thought to be a common practice in Southeast Asia. This article aimed to explore the demographics of the patient who had illicit penile augmentation, its complications, surgical methods employed for removal as well as the long-term outcome following treatment, specifically on sexual satisfaction. Method. Records of patients with a penile foreign body to the Reconstructive Science Unit were retrieved. Demographics, presenting symptoms, surgical methods and outcomes were recorded and analyzed. Results. A total of 14 patients was identified. The median age at implantation and duration is 36 years old and 48 months respectively. The penile subdermal injection was the sole method utilized with the use of liquid silicone in 7 patients. Constant pain, painful erection, and discomfort were common symptoms (42.8%). All patients underwent surgical excision followed with either native (penile skin) full-thickness skin graft (FTSG), distant donor FTSG or primary closure. Five out of 7 patients report improved sexual satisfaction post-surgery. Conclusion. This report demonstrated two groups of men with distinct age, duration of implant and possibly differing motivation for penile augmentation. The various complications presented stem from inflammation and scarring. Distant FTSG donor has a superior take rate compared to native FTSG. Long term outcome following treatment on sexual well-being is generally good. Illicit penile augmentation is generally unsafe, however, a large-scale study is required to establish the prevalence of the practice.